Understanding Consumer Behavior in Marketing Management: A Descriptive Study and Review of Literature - Rusdian, Suca; Sugiat, Jajang; Tojiri, Yusuf (Manunggal Halim Jaya, 2024)
This research aims to explore the multifaceted nature of consumer behavior in marketing management by synthesizing literature on individual characteristics, social influences, cultural factors, and technological advancements. The study employs a comprehensive review methodology to analyze existing research findings and identify key insights into consumer decision-making processes and preferences. Drawing from diverse disciplines such as psychology, sociology, and marketing, the research investigates the interplay between individual traits, social dynamics, cultural norms, and technological innovations in shaping consumer behavior patterns. Methodologically, the study utilizes a systematic literature review approach to collate and analyze relevant literature, identifying common themes, theoretical frameworks, and empirical findings. The results of the research reveal the significant impact of individual characteristics, such as personality traits and values, on consumer preferences and purchasing behaviors. Moreover, social influences, including social identity theory and reference groups, emerge as critical determinants of consumer decision-making processes. Cultural factors, as elucidated by Hofstede's cultural dimensions theory, play a pivotal role in shaping consumer attitudes and behaviors across diverse cultural contexts. Additionally, technological advancements, particularly in social media and artificial intelligence, have transformed consumer behavior patterns, creating new opportunities and challenges for marketers. The findings underscore the importance of understanding the complex interactions between individual, social, cultural, and technological factors in designing effective marketing strategies.